Hubungan Antara Sikap Kerja dan Motivasi Kerja dengan Kinerja Pengelola Sikda Generik Puskesmas di Kabupaten Ogan Komering Ulu Timur Tahun 2022 - Wastiti Handayani (Syntax Corporation, 2023)
Based on the need for a standardized and integrated health data system that can be carried out in real time, since 2018, a generic regional health information system (SIKDA) has been implemented in East Ogan Komering Ulu Regency (OKU Timur) to accommodate this need. Implementation of this generic SIKDA aims to provide accurate, precise, and fast health data and information that is useful to provide convenience in policy making, so that it is expected to be able to provide good performance. So that in its implementation it can perform well, it is necessary to have a driving factor, including work attitude and work motivation. This study aims to determine the relationship between work attitude and work motivation and the performance of the Public Health Center Generic SIKDA Management in East OKU District. This study uses a cross-sectional research design. The results of the study showed that both work attitude and work motivation variables had a significant relationship with the performance of the Public Health Center Generic SIKDA Manager in East OKU District.